Cluster Randomized Controlled Trial of a Breathing and Relaxation Training Included in Antenatal Education - Leutenegger V, Daly D, Sultan-Beyer L, Weingart T, Pehlke-Milde J, and Wieber F. (Elsevier, 2026)
Objective: To evaluate the effectiveness of the BreLax antenatal education class, which includes breathing and relaxation techniques, to improve childbirth self-efficacy compared with standard antenatal education. Design: Parallel-group, cluster-randomized controlled trial. Setting: Hospital-based antenatal classes in Switzerland. Participants: Pregnant women (N = 64: intervention n = 35; control n = 29) from 32 antenatal education classes randomized at the class level (16 intervention classes and 16 control classes). Methods: All participants attended an 8-hour antenatal education class. We assessed childbirth self-efficacy as the primary outcome using validated measures and maternal and neonatal outcomes. The intervention group also received structured and guided breathing and relaxation training supported by digital tools. Results: Childbirth self-efficacy improved significantly from baseline to after intervention in both groups (intervention: +14.1 points, p < .001; control: +11.2 points, p = .00), with no significant interaction between time and study arm (p = .58). Greater frequency of self-practice of the breathing and relaxation technique taught in the BreLax intervention predicted greater self-efficacy (ß = –6.16, p = .05). We observed no group differences for childbirth experience or neonatal outcomes except for perceived safety, which was slightly higher in the control group (p = .04). Conclusion: Antenatal education that includes structured breathing and relaxation techniques, such as the BreLax intervention, can support the development of childbirth self-efficacy. Greater frequency of self-practice of these techniques was associated with higher self-efficacy, which underscores the importance of repeated and supported practice. Future researchers should further examine the optimal intensity of practice, the role of partner involvement, and the potential of digital tools to facilitate sustained engagement with breathing and relaxation techniques.
PUBLISHED
Keywords: midwifery; parturition; pregnancy; prenatal care; prenatal education; Health outcomes; Maternal health and maternal morbidity; Maternity Care; Midwifery; Pregnancy; Health